Current developments in small cell lung cancer - Aydınalp Camadan, Yasemin (Scientific Reports in Medicine, 2024)
Small cell lung cancer (SCLC), often associated with smoking, is characterized by its aggressive biology and potential for early metastasis. It accounts for approximately 15% of all lung cancer patients. The combination of platinum-based chemotherapy and etoposide has been used for many years in the treatment of SCLC. The prognosis for patients with SCLC who are treated as a single group is still quite poor. Recent research has provided a new perspective on the biology of SCLC. A survival benefit has been demonstrated by adding immune checkpoint inhibitors to chemotherapy in patients with extensive stage SCLC. The study of the molecular, biological, and immunological properties of the heterogeneous structure of SCLC is a promising area of research for the future. Identification of distinct gene expression profiles (ASCL1, NEUROD1, POU2F3, and YAP1) of SCLC patients may form the basis of the most effective and individualized therapeutic treatments in disease management. More research is needed to identify SCLC subtypes and develop effective treatments for this group of patients who have a poor prognosis.